A brief study on bats of Pokhara Valley - Koju, Narayan P.; Chalise, Mukesh K. (Journal of Science and Engineering, 2012)
There is very less information on bats in Nepal. Pokhara valley provides suitable habitat for both microchiroptera and mega-chiroptera. This valley has variable topographical features and climatic conditions, which is favorable for bats. A two week long observation was carried out on bats and their roosting sites in December 2010 and February 2011. Eleven roosting sites were observed and three species of bat were captured from different roosting sites. Mist net and Gully net were used to capture the bats. Bats in Chamero Gupha were counted and found to have density of 94.57 per sq. meter; population of Pteropus giganteus was counted in Radha Krishna Tole.